Efficient Localization and Data Routing for Better Usage in Case of Wireless Sensor Networks: Optimizing Energy Efficiency and Security in Wireless Sensor Networks (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Survey of all the receiver-initiated MAC protocols and presents their unique optimization features, which deal with several challenges of the link layer such as mitigation of the energy consumption, collision avoidance, provision of Quality of Service (QoS) and security. Focusing on the particular requirements of an energy harvesting application, the dissertation contin-ues with the presentation of a MAC protocol, named On Demand MAC (ODMAC), which extends the receiver-initiated paradigm with several energy-efficient features that aim to adapt the consumed energy to match the harvested energy, distribute the load with respect to the harvested energy, decrease the overhead of the communication, address the requirements for collision avoidance, prioritize urgent traffic and secure the system against beacon replay attacks.